Прогнозирование индикаторов цели в рамках регионального мониторинга социально-экономического развития - Мордовцев, Александр Сергеевич (Таврический национальный университет им. В. И. Вернадского, 2013)
В статье рассмотрены основные этапы мониторинга социально-экономического развития, являющегося основным подготовительным этапом регионального индикативного планирования. Отражены проблемы социально-экономического прогнозирования, дан краткий обзор методов, позволяющих получить прогнозные значения индикаторов цели, определяющих структуру индикативного плана СЭР региона. Дан пример прогноза уровня задолженности по заработной плате населению АРК.

One of the most effective mechanisms for the implementation of the strategic targets of the development of the region is indicative planning. According to the author, the essence of the territorial indicative planning is that under the conditions of unity and contradictions of the opposite interests of the state, the private business and the community an opportunity appears to smooth over the contradictions by implementing coordinated, acceptable for all parties indicative plans which are formed in accordance with scientifically substantiated priorities and objectives of the strategic and sustainable development of the region territories (based on the social and economic development monitoring), effective mechanisms of state regulation of state – private business partnership in the system of effective management of the regional development. Indicative plan is a comprehensive document, which presents the aim indicators that define the main directions of regional development, mechanisms for achieving aims, the participants of the planning process and necessary material and financial resources. The aim of this paper is to identify the problems of forecasting aim indicators that define the structure of the indicative plan. Main stages of the social and economic development monitoring, which is the basic preparatory stage of the regional indicative planning have been analyzed in the article. After system analysis of levels and trends of regional development, determine status indicators which used in the process of developing short-and medium-term forecasts, the result of which is the definition of threshold values of aim indicators for different development scenarios. Analysis of indicative plans of municipalities of the Russian Federation and certain administrative regions of Ukraine has shown that up to now there is no consensus on the composition of the aim indicators. At the same time, the solution of the problem of unification of plans must be resolve in compliance with specific character of development of a particular territorial unit. Experts from the planning regional council of state administration must take the final decision on the choice of aim indicators consider aspects and specific features of the regional development. Problems related with the collection and creation of databases, poor institutional legal services, are absence reason of a unified methodology of socio-economic forecasting, that affecting the credibility and quality of predictive results. The article describes the main stages of social and economic forecasting, provides an overview of methods that help to conduct the forecast of aim indicators. The example of the forecast of the wage arrears level for the population of the Autonomous Republic of Crimea has been given.
Forecast of the indicators within the framework of the regional monitoring of social and economic development
Keywords: индикативное планирование; региональное развитие; прогнозирование; индикатор; мониторинг; prognostication; indicator; monitoring; planning; development